2006
DOI: 10.1111/j.1472-765x.2006.01945.x
|View full text |Cite
|
Sign up to set email alerts
|

Nanobacteria - propagating calcifying nanoparticles

Abstract: Nanobacteria, also known as calcifying nanoparticles (CNP), are controversial infectious agents not matching the current criteria for ‘living organism’. Despite the controversy of their classification, they propagate and cause cell death in vitro and are associated or found in many human diseases. Thus, more efforts should be focussed on research on pathogenicity of CNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
59
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 17 publications
0
59
0
6
Order By: Relevance
“…The intriguing characteristics of human nanobacteria include extremely small size from 80 to 500 nm (12), 0.2-m filterability (3), widespread abundance in animals and humans (11), as well as nucleation of HAP (2). These unusual characteristics actually lead to the suggestions that nanobacteria may represent an overlooked primitive form of life (13) with the smallest cellular dimension known on Earth (14).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The intriguing characteristics of human nanobacteria include extremely small size from 80 to 500 nm (12), 0.2-m filterability (3), widespread abundance in animals and humans (11), as well as nucleation of HAP (2). These unusual characteristics actually lead to the suggestions that nanobacteria may represent an overlooked primitive form of life (13) with the smallest cellular dimension known on Earth (14).…”
mentioning
confidence: 99%
“…More importantly, they showed that HAP could be propagated similarly to a bacterial subculture; they also reattributed the published nanobacteria 16S rDNA sequence to an occasional contaminant of PCR reagents. However, the nanobacteria field has largely ignored these important findings and, in recent years, has continued to host a flurry of research (10,20) and review papers (11,24) that purport to find a pathogenic role for nanobacteria in various disease processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Nanobacteria is the name of a proposed class of living organisms specifically cell-walled microorganisms with a size much smaller than the generally accepted lower limit size for life (about 200 nanometers for bacteria). 5 Neva et al (1992) found unusual thin slimy film developing on the culture surfaces while working on mammalian cell cultures. Using scanning electron microscope, they found 20 to 200 nanometer sized bacteria in calcified shells.…”
Section: Introductionmentioning
confidence: 99%
“…So, the controversy persisted. Certainly, there was consensus that living or nonliving NB did cause many diseases associated with calcifi cation of soft tissues, viz., arterial heart disease, kidney stones, gall stones and gall bladder infl ammation 5 .The two recent papers by Kajander's group discuss the present status 6,7 . A more descriptive term "Calcifying Nano Particles (CNP)" has been coined for the so-called nanobacteria.…”
mentioning
confidence: 99%